2017
DOI: 10.2106/jbjs.16.00791
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of Computer-Navigated Compared with Conventional Knee Arthroplasty in the Same Patients

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…As the use of technology-assisted surgery has increased over the past 2 decades, multiple studies have demonstrated improved mechanical alignment with the use of computer navigation and robot-assisted surgeries [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . However, studies have not been conclusive regarding the effects of technology assistance on revision rate, patient-reported outcomes, and complication rates [12] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] . Given the lack of conclusive data, the debate concerning the value of technology-assisted TKA and its cost-effectiveness continues.…”
Section: Introductionmentioning
confidence: 99%
“…As the use of technology-assisted surgery has increased over the past 2 decades, multiple studies have demonstrated improved mechanical alignment with the use of computer navigation and robot-assisted surgeries [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . However, studies have not been conclusive regarding the effects of technology assistance on revision rate, patient-reported outcomes, and complication rates [12] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] . Given the lack of conclusive data, the debate concerning the value of technology-assisted TKA and its cost-effectiveness continues.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the use of ABN for TKAs is no guide to rotational alignment, another important predictor of longterm survivorship and functional outcomes. 50,51 Rotation is therefore guided in the same approach to CONV and no study to date has evaluated if a difference exists in rotational alignment to other techniques. Other limitations include the lack of information regarding verification of bone resections, costs and inability to assess soft tissue balancing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies so far did not show any significant differences of clinical function, position, and survivorship of the components between conventional approach and computer assisted systems in long-term follow-up over 12 years for knee replacement. 35 On the other hand, it appears that we will see more navigation and robotic systems involvement for arthroplasty operations in the near future. Finally, 'getting it right first time' by using the most reliable implants with proven survivorship 29 is one of the main key factors in the success of arthroplasty.…”
Section: Discussionmentioning
confidence: 99%